Fault tolerance mechanism of agent-based distributed event system - Sahingoz, Ozgur Koray; Sonmez, A. Coskun (SPRINGER-VERLAG BERLIN, 2006)
Event based system development is increasingly becoming popular for large-scale and heterogeneous distributed platforms because it helps diminishing software dependencies, and enhancing system integration and evolution. The architecture of an event based system should be tolerant to error and network fallout especially in dispatching service. Throughout the entire design of event based systems, fault-tolerance mechanism plays very important role in developing large scale middleware. This is a crucial quality of service where node failures are frequent in wide area networks with many brokers. In this paper, we address fault tolerance mechanism of the agent based distributed event system where events are responsible for determining their own paths, in the case of link and broker failures. This mechanism is achieved by dynamically configuring new paths at run time for making the system more scalable and robust on a global scale.
Keywords: Computer Science